Estrategias de venta en el Bazar Catita de la Ciudad de Babahoyo. - García Cevallos, Adriana Alejandra (2022)
Sales are an essential part of companies because through them it is possible to achieve the established commercial objectives and also allow the development of a competitive advantage over the competition. Reason why every organization must develop strategies that help generate greater economic benefits such as; Increase sales and retain customers. The objective of the case study is to analyze the sales strategies through a situational diagnosis of Bazar Catita, to measure the efficiency of the commercial establishment in terms of carrying out actions that help increase the profitability of the business and greater positioning in the local market. The methodology used in this research was made up of a qualitative approach, the method used was inductive, and the types of research are: descriptive and documentary, since it allowed describing the situations identified in the bazaar regarding sales strategies. The technique applied was the interview with the owner of the business to collect information on the problem. The results of the investigation allowed us to know that in the commercial establishment there are a series of problems that affect its growth, such as: weak administration, lack of application of strategic sales and marketing strategies, it does not have automation of sales processes, makes use of digital tools to increase sales, among other problematic situations. It was concluded that the absence of marketing strategies that help increase sales prevents increasing profitability, attracting customers and improving the economic benefits of the business.